Methods for the detection of tumor-specific single nucleotide somatic mutations in plasma cDNA samples - L. M. Dyakov; O. M. Krivtsova; P. A. Khesina; I. F. Kustova; N. A. Dyakova; N. S. Muge; N. E. Kudashkin; Yu. I. Patyutko; N. L. Lazarevich (Успехи молекулярной онкологии)
Introduction. Liquid biopsy is considered as a minimally invasive method of molecular genetic analysis that can be used for early diagnosis, prognosis of disease development, monitoring of residual disease or treatment outcomes, and selection of optimal drug therapy schemes for a patient. Along with the development of tests based on the study of panels of oncologically significant genes or their regions, for various forms of genetically heterogeneous tumors a promising approach could be the use as an object of liquid biopsy of an individual spectrum of somatic mutations of a particular patient that can be detected on the basis of high-throughput sequencing of tumor tissue.Aim. To determine the applicability of different methods for detecting single-nucleotide somatic mutations detected in tumor tissue of a particular patient in cDNA preparations from blood plasma obtained before surgical removal of the tumor and to evaluate the possibility of quantifying the proportion of the alternative variant in the total pool of cDNA. Materials and methods. We used normal and tumor tissue, as well as blood plasma samples from patients with hepatocellular carcinoma, and various methods for detecting single-nucleotide somatic mutations: real-time polymerase chain reaction (PCR) with intercalating dye or with TaqMan probes, droplet digital PCR and high-throughput sequencing of target amplicons.Results. Using the example of a somatic mutation in the TLN1 gene detected in tumor tissue of a patient with hepatocellular carcinoma, methods were developed and tested, each of which allows specific detection of the mutant variant in small amounts (2 ng) of cDNA from the blood plasma of the same patient. The use of droplet PCR and target amplicon sequencing methods allowed us to quantify the proportion of the mutant variant in the total cDNA pool, which was 19.7 and 23.5 %, respectively.Conclusion. Among the methods investigated, droplet digital PCR and targeted amplicon sequencing allow not only reliable detection of mutant variants in small amounts of cDNA, but also adequate quantification, which is particularly important for the development of ways to monitor tumor growth during treatment. The close values of the proportion of mutant variants in cDNA detected by these methods indicate the accuracy of quantitative analysis and the possibility of their use for cross-validation of the results obtained.